UJI AKTIVITAS ANTIDIABETES AKAR KAYU KUNING (ARCANGELISIA FLAVA) - Fatmawati Karim; Susilawati Susilawati; Liniyati D Oswari; Dzakiyah Dzakiyah; Fahira Anindita (Fakultas Kedokteran Universitas Sriwijaya, 2020)
This study used extracts of Arcangelisia flava root to see its potential as an antidiabetic activity that can reduce blood glucose levels in male wistar mice induced by alloxan.The study design was an in vivo experimental study with a post test with control group design approach. The samples were 70 male wistar mice divided randomly into 14 treatmen groups, which every group contained five rats : negative control (NaCMC 0.5%), positive control (acarbose 4.5 mg / kgBW), hexane extract of Arcangelisia flava root (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW), ethyl acetate extract of Arcangelisia flava root (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW), ethanol extract of Arcangelisia flava root (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW), and aquadest extract of Arcangelisia flava root (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW). All treatmen groups were subjected to alloxan induction to reach a glucose level af approximately 200 mg/dL (pretest). After 15 days, a measurement of blood glucose (posttest) was taken. The results showed that ethanol extract 750 mg/kgBW, ethyl acetate extract (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW) and aquadest extract (dose 250 mg/kgBW, 500 mg/kgBW and 750 mg/kgBW) have the ability to reduce blood glucose and only ethyl acetate dose 750 mg/kgBW, aquadest extract dose 500 mg/kgBW and 750 mg/kgBW can reduce blood glucose likely acarbose. Phytochemical tests found the presence of alkaloids and flavonoids in ethanol extract, ethyl acetate extract and aquadest extract, but tannin contained only in ethanol extract and ethyl acetate extract.